Extraction of lipopolysaccharide from fish-derived Aeromonas hydrophila and their immunostimulatory effect on Qihe crucian carp - Xinxin Liu; Yiran Wang; Junli Wang; Xiao Yan; Liping Yang; Chaobin Qin; Guoxing Nie (Aquaculture and Fisheries)
Purified lipopolysaccharide (LPS) was first obtained from fish-derived Aeromonas hydrophila (A. hydrophila) by hot phenol-water combined with enzymatic hydrolysis. Subsequently, different concentrations of LPS (0, 0.2, 0.4, 0.8, and 1.2 mg/mL) were injected intraperitoneally into Qihe crucian carp (Carassius auratus var. Qihe) with a dose of 3 μL/g body weight to evaluated their immunostimulatory activity by detecting the expression of immune-related genes in the spleen, head kidney, and hepatopancreas. The results showed that the average extraction rate of LPS was about 1.063% based on the precipitation weight of wet bacteria, of which the polysaccharide content was 9.39%. The silver staining band of LPS after SDS-PAGE electrophoresis showed a ladder distribution typically characterized by smooth-type LPS. Protein and nucleic acid electrophoresis results showed very low amounts of residual protein and nucleic acid, and high-performance liquid chromatography (HPLC) results showed that the purity of the extracted A. hydrophila LPS was similar to that of high-purity commercial LPS. Pro-inflammatory cytokine genes such as IL-1, IL-8, TNF-α, and IL-6 were more sensitive to LPS stimulation than anti-inflammatory factors such as IL-10 and TGF-β. After 2 h of injection, their expression levels in the spleen, head kidney, and hepatopancreas were significantly increased (P < 0.05), with the 0.8 and 1.2 mg/mL injection groups showing the most significant increase. The gene expression of IL-10 and TGF-β showed slight fluctuations in response to A. hydrophila LPS stimulation (P < 0.05). In conclusion, high-purity LPS was extracted from A. hydrophila derived from fish by modified hot phenol-water method, it demonstrating that LPS product could significantly regulate the innate immunity of Qihe crucian carp, with the most effective vaccination dose being 2 mg/kg/BW. These findings provide useful information for future research on endotoxin vaccines.